The anti-cholestatic effects of Coptis chinensis Franch. alone and combined with Tetradium ruticarpum (A. Jussieu) T. G. Hartley: dual effects on fecal metabolism and microbial diversity - Jun Han; Peijie Wu; Zongying Xu; Chao Liu; Qian Chen; Fenghua Zhang; Huan Tao; Dan Luo; Li Zhou; Bo Wang; Zhe Gao; Tao Shen; et al. (Frontiers Media S.A., 2024)
Introduction: Drug dosages and combinations are the main factors that affect the efficacy of pleiotropic traditional Chinese medicine (TCM). Coptis chinensis Franch. (CF) is a representative TCM with multiple effects and is often combined with Tetradium ruticarpum (A. Jussieu) T. G. Hartley (TR) to treat cholestasis. The present study assessed the influence of CF dose and its combination with TR on the efficacy of CF in cholestasis treatment, including their effects on fecal metabolism and fecal microorganisms.Methods: Rats with α-naphthylisothiocyanate (ANIT, 50 mg/kg)-induced cholestasis were administered low (0.3 g/kg) and high (0.6 g/kg) doses of CF, as well as CF combined with TR at doses of 0.6 g/kg and 0.9 g/kg, respectively. The anti-cholestatic effects of these treatments were assessed by determining their anti-inflammatory, hypolipidemic, and anti-oxidative stress properties. Additionally, fecal metabolomics and fecal microorganisms were analyzed.Results: Low dose CF had a more potent hypolipidemic effect than high dose CF, whereas high dose CF had more potent anti-inflammatory and anti-oxidative stress effects. Combination with TR enhanced the hypolipidemic effect, but antagonized the anti-inflammatory effect, of CF. Analyses of fecal metabolomics and fecal microorganisms showed differences in the regulation of lipid- and amino acid metabolism-related pathways, including pathways of linoleic acid, tyrosine, and arachidonic acid metabolism, and amino acid biosynthesis between different doses of CF as well as between different doses of CF in combination with TR. These differences may contribute to differences in the anti-cholestatic effects of these preparations.Conclusion: CF dose influences its anti-cholestatic efficacy. The combination with TR had synergistic or antagonistic effects on the properties of CF, perhaps by altering fecal metabolism and fecal microbial homeostasis.